Individualised antibiotic dosing for patients who are critically ill: challenges and potential solutions - Roberts, Jason A.; Abdul Aziz, Mohd. Hafiz; Lipman, Jeffrey; Mouton, Johan W.; Vinks, Alexander A.; Felton, Timothy W.; Hope, William W.; Farkas, Andras; Neely , Michael N.; Schentag, Jerome J.; Drusano, George; Frey, Otto R.; et al. (Elsevier, 2014)
Infections in critically ill patients are associated with persistently poor clinical outcomes. These patients have severely altered and variable antibiotic pharmacokinetics and are infected by less susceptible pathogens. Antibiotic dosing that does not account for these features is likely to result in suboptimum outcomes. In this Review, we explore the challenges related to patients and pathogens that contribute to inadequate antibiotic dosing and discuss how to implement a process for individualised antibiotic therapy that increases the accuracy of dosing and optimises care for critically ill patients. To improve antibiotic dosing, any physiological changes in patients that could alter antibiotic concentrations should first be established; such changes include altered fluid status, changes in serum albumin concentrations and renal and hepatic function, and microvascular failure. Second, antibiotic susceptibility of pathogens should be confirmed with microbiological techniques. Data for bacterial susceptibility could then be combined with measured data for antibiotic concentrations (when available) in clinical dosing software, which uses pharmacokinetic/pharmacodynamic derived models from critically ill patients to predict accurately the dosing needs for individual patients. Individualisation of dosing could optimise antibiotic exposure and maximise effectiveness.